Highly Effective mRNA-LNP Vaccine Against Respiratory Syncytial Virus (RSV) in Multiple Models - Huarong Bai; Xueliang Yu; Yue Gao; Qin Li; Baigang Wen; Rongkuan Hu (Vaccines)
Background: The transmembrane fusion (F) protein of RSV plays important roles in RSV pathogenesis as it mediates the fusion between the virus and the target cell membrane. During the fusion process, the F protein transits from a metastable state (prefusion, preF) to a stable state (postfusion, postF) after the merging of the virus and cell membranes. The majority of highly neutralizing antibodies induced by natural infection or immunization target the preF form, which makes it the preferred antigen for vaccine development. Methods: Here, we designed an effective RSV mRNA vaccine, STR-V003, consisting of mRNA encoding preF protein in lipid nanoparticles (LNPs). The immunogenicity, protection efficacy and toxicity were measured in multiple animal models. Results: STR-V003 demonstrated robust immunogenicity in both mice and cotton rats, inducing high levels of neutralizing antibodies and RSV preF-specific IgG antibodies and significantly reducing the RSV viral loads in the lung and nose tissue of challenged animals. In addition, STR-V003 did not show significant enhancement of lung pathology without causing vaccine-enhanced disease (VED). The repeated dose general toxicology studies and local tolerance studies of STR-V003 were evaluated in rats and non-human primate (NHP). Conclusions: STR-V003 demonstrates a favorable safety profile and induces robust protective immunity against RSV.